PERSEPSI MASYARAKAT TERHADAP KEBERADAAN PANGKALAN PENDARATAN IKAN (PPI) SELILI SAMARINDA - Ilma Yuliana Boa; Eko Sugiharto; Fitriyana (2339-1324, 2015)
This study aims to identify and describe forms The Community Perception Against Port Fishes Suppliers in Selili Samarinda and role of Port Fishes Suppliers in Selili Samarinda for increase the community’s knowledge to presence a Port Fishes Suppliers in Selili Samarinda. The method used in this thesis is a survey. The type of data used is primary and secondary type and the data analysis technique is a quantitative analysis. The Port Fishes Suppliers Selili Samarinda located in Selili Vilage, District of Samarinda Ilir, in Samarinda City which is among the central marketing of fishery supplies both both marine fish and freshwater fish which is strategically located in the path of Mahakan River landing activities. The Port Fishes Suppliers Selili Samarinda has important role in the fulfillment of fish stocks for the community in Selili. However, it is not felt for the people themselves directly because people prefer to deal directly with retailers of fish / fish sellers in the market. This is proven by the public perception of the existence of PPI is only 15 respondents out of 40 respondents are aware PPI Selili in Samarinda.